Transcranial cortex-wide Ca2+ imaging for the functional mapping of cortical dynamics - Yamada, Serika; Wang, Yan; Monai, Hiromu (Frontiers in Neuroscience, 2023)
Visualization and tracking of the information flow in the broader brain area are essential because nerve cells make a vast network in the brain. Fluorescence Ca2+ imaging is a simultaneous visualization of brain cell activities in a wide area. Instead of classical chemical indicators, developing various types of transgenic animals that express Ca2+-sensitive fluorescent proteins enables us to observe brain activities in living animals at a larger scale for a long time. Multiple kinds of literature have reported that transcranial imaging of such transgenic animals is practical for monitoring the wide-field information flow across the broad brain regions, although it has a lower spatial resolution. Notably, this technique is helpful for the initial evaluation of cortical function in disease models. This review will introduce fully intact transcranial macroscopic imaging and cortex-wide Ca2+ imaging as practical applications.